Social Media Marketing's Effect On Customer Satisfaction - Frans Sudirjo; I Nyoman Tri Sutaguna; Rina Sovianti; Arief Yanto Rukmana; PA. Andiena nindya putri (Pusat Riset dan Inovasi Nasional, 2023)
Human wants are limitless. Primary needs, secondary needs, and tertiary needs are the three sorts of needs that humans have. All of these requirements, especially basic requirements, are critical to human survival. The fundamental necessities themselves are food, clothing, and shelter, i.e. the need for important goods like clothing, food, and shelter. The most crucial element is the necessity for a place to live, a place to dwell or what we often refer to as home, as a place for us to take refuge and socialise with the environment. As a result, many people desire a suitable place to reside. This study took a quantitative approach, with 195 persons chosen utilising the Accidental Sampling technique. Multiple regression analysis reveals that all independent factors (product quality and price) have a positive effect on purchase intent.